2015
DOI: 10.4314/ajtcam.v12i6.1
|View full text |Cite
|
Sign up to set email alerts
|

Propolis and bee venom in diabetic wounds; a potential approach that warrants clinical investigation

Abstract: Background: Wound healing in diabetes mellitus is a complex multi-stage process that requires the proper function of multiple systems. The mechanisms of impaired wound healing of diabetic wounds are still poorly understood. Therefore, various interventions are being used for wound management without great success. Bee products have various properties that make them an important addition to the diabetic wound management. Methods: This review summarized previous and recently published papers of the effects of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Topically applied propolis decreased persistent inflammatory in diabetic wounds by normalizing neutrophil and neutrophil elastase. Caffeic acid is responsible for anti-inflammatory effect of propolis [55]. Genistein from propolis accelerated wound healing and stimulated wound angiogenesis in mice with diabetes type-1 [56].…”
Section: Propolismentioning
confidence: 99%
See 1 more Smart Citation
“…Topically applied propolis decreased persistent inflammatory in diabetic wounds by normalizing neutrophil and neutrophil elastase. Caffeic acid is responsible for anti-inflammatory effect of propolis [55]. Genistein from propolis accelerated wound healing and stimulated wound angiogenesis in mice with diabetes type-1 [56].…”
Section: Propolismentioning
confidence: 99%
“…Genistein from propolis accelerated wound healing and stimulated wound angiogenesis in mice with diabetes type-1 [56]. Furthermore propolis may be effective in healing in different animal models including animals with burns and diabetic wounds [3,55,56]. Moreover propolis is highly effective in the treatment of Acne vulgaris.…”
Section: Propolismentioning
confidence: 99%
“…Pseudomonas aeruginosa have been identified to account for 20-40% of wound infection and 5-15% nosocomial infections respectively, with infection mainly following surgery and burns [6]. Studies in other polymicrobial chronic infections suggest that the presence of specific pathogens is more important than that of the bacterial burden [7,8], contributing to the non-healing outcome in acute and chronic wound infections.…”
Section: Staphylococcus Aureus Andmentioning
confidence: 99%
“…These data indicated that bee venom and propolis have potential therapeutic properties in chronic diabetic wound, and the use of propolis and/or bee venom can be new effective intervention in clinical practice. However, their therapeutic effects should be proved by clinical studies, focusing on the advantage of using these agents over the current interventions, particularly in respect of therapeutic activities, safety, and cost effectiveness (Al‐Waili et al, ).…”
Section: Propolismentioning
confidence: 99%
“…Al-Waili et al, 2015;Boufadi et al, 2014;Falcão et al, 2014Corrêa et al, 2017;Hozzein et al, 2015;Iyyam Pillai et al, 2010;McLennan et al, 2008)(Henshaw et al, 2014) …”
mentioning
confidence: 99%